Naturalismo biológico: a solução dualista de John Searle para o problema mente-corpo - Lima Filho, Maxwell Morais de (2010)
The objective of this work is to propose a classification of John Searle‟s biological naturalism in one of theoretical conceptions of Philosophy of Mind. In order to do that, I will present a panoramic vision of principal theories and a presentation of theses of biological naturalism in order to compare this with those. Searle himself resist to label the biological naturalism since, according him, all theories of tradition in Philosophy of Mind start from a mistaken assumption, that is, the conceptual dualism, according to which there is a mutual exclusion between the physical and mental categories: the physical is not mental, and mental is not physical. For Searle, mental phenomena are biological and, therefore, physical. However, this does not mean that there is an ontological reduction of mental to physical, because there is an ontological distinction between these two levels – first-person ontology and third-person ontology, respectively. The problem is that with such ontological distinction, Searle ends up creating a new kind of dualism, that instead of countering the physical to the mental, opposes the objective (third-person ontology) to the subjective (first-person ontology). By defending the ontological physicalism and, at the same time, to endorse that mental events are real, causally effective and ontologically irreducible, Searle‟s conception converges at many points with the non-reductive physicalism and property dualism. I will compare the biological naturalism with both theories and – at the end – I will have subsidies to argue why classify it in one and not the other.